Winner of the SLS Annual Conference Best Paper Prize 2015: Towards an understanding of the basis of obligation and commitment in family law. (March 2016) - Douglas, Gillian
Abstract : Much family law scholarship in recent years has been focused on the recognition of different types of family relationship. Often, the rationale for the grant of rights and duties to new forms of relationship is said to be because the parties have shown commitment, or the same degree of commitment, as those in formally recognised unions, such as marriage. But there has been relatively little consideration of why or how commitment can provide an adequate rationale for the imposition of legal consequences, in particular, legal obligations, especially when such commitment may be lacking on the part of one of the parties, or comes to an end. This paper explores the meanings of obligation and commitment within the family and questions whether commitment provides a necessary or sufficient justification for the imposition of legal obligations in family relationships.